16S rRNA gene sequence of local isolate of new strain of Bacillus that produces alkaline phosphatase - Al-Hilli, Hassan Majeed Rasheed; Al-Taie, Khamael Lutfi Shakir (World Journal of Experimental Biosciences, 2015)
Twenty one bacterial isolates were obtained from different sources, 9, 9 and 3 isolates of Bacillus were isolated from different kinds of food, soil and water, respectively. They were identified according to morphological of their colonies and biochemical tests. The results showed that all of them belong to the genus Bacillus. Bacillus FH4 isolate (isolated from potato) was determined as the highest producer of alkaline phosphatase (1.433 U/ml). Bacillus FH4 isolate was identified by 16s rRNA, the phylogenetic tree was done by MEGA5 program. The isolate was closet to Bacillus lichenifrmis, the bacterial strain was submitted to NCBI and specified as Bacillus licheniformis FH4. IRQ with accession number KF531930.
Keywords: Alkaline phosphatase, Bacillus, 16S rRNA.